2020
DOI: 10.4314/jasem.v24i6.14
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Heavy Metals in Vegetables Cultivated around Dumpsites in Jimeta and Ngurore Areas, Adamawa State, Nigeria

Abstract: The study analyses the health risk assessment of the concentration of Iron, Lead, Copper, Chromium, and Cadmium heavy metals in vegetables grown near dumpsites of Jimeta and Ngurore areas of Adamawa State, Nigeria. Vegetables mainly Spinach (Spinacia oleracea) and lettuce (Lactuca sativa) were collected in triplicates and analyzed using Atomic Absorption Spectrophotometer Buck 210VGP (AAS). The result revealed that heavy metals detected in spinach at Jimeta dumpsite decreased in the following order: Fe (3.7 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…The Manganese value (1.220±0.017mg/kg) in this study corresponds to the manganese value recorded in green vegetable (Amaranthus hybridus)from Owode farm [24]. The value of Copper (0.199 ±0.002mg/kg) reported in this study is slightly higher than the copper value (0.1383 mg/kg) )reported for Spinach near Ngurore dumpsite [22].…”
Section: Discussion Of the Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…The Manganese value (1.220±0.017mg/kg) in this study corresponds to the manganese value recorded in green vegetable (Amaranthus hybridus)from Owode farm [24]. The value of Copper (0.199 ±0.002mg/kg) reported in this study is slightly higher than the copper value (0.1383 mg/kg) )reported for Spinach near Ngurore dumpsite [22].…”
Section: Discussion Of the Resultssupporting
confidence: 68%
“…At the Ipaja farm, Sakiyo, et al [22] reported Lead in a Spinach near dumpsite as 0.1766 mg/kg, this value is lesser than 2.011±0.003 mg/kg recorded in this study, while the lead value ( 2.98mg/kg) reported for Amaranthus © 2022 Conscientia Beam. All Rights Reserved.…”
Section: Discussion Of the Resultscontrasting
confidence: 65%
See 3 more Smart Citations